2018
DOI: 10.1111/ppa.12960
|View full text |Cite
|
Sign up to set email alerts
|

Induction of resistance against pine wilt disease caused by Bursaphelenchus xylophilus using selected pine endophytic bacteria

Abstract: Pine wilt disease (PWD) is the most destructive disease threatening pine worldwide. The disease is mainly caused by the pine wood nematode, Bursaphelenchus xylophilus, which is vectored by pine sawyer longhorn‐beetles, Monochamus spp. This study aimed to select resistance‐inducing pine endophytic bacteria for management of PWD. To set up a defence‐related genes expression pattern for screening, four chemical inducers (salicylic acid, γ‐aminobutyric acid (GABA), β‐aminobutyric acid and α‐aminobutyric acid) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Regarding PWN, chemical inducers such as γ-aminobutyric acid, were found to trigger the expression of certain pathogenesis-related genes and, consequently, PWD severity was reduced in treated seedlings. Furthermore, specific pine endophytic bacterial species were utilized for induction of resistance against PWD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding PWN, chemical inducers such as γ-aminobutyric acid, were found to trigger the expression of certain pathogenesis-related genes and, consequently, PWD severity was reduced in treated seedlings. Furthermore, specific pine endophytic bacterial species were utilized for induction of resistance against PWD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Distilled water containing 250 μg/mL Tween 20 was used as an untreated control and 5 replicates were maintained for each treatment. Disease severity in treated seedlings was evaluated at 30 days post-inoculation, according to a scale from 0 to 5, in which 0 = healthy seedlings with normal green needles, 1 = < 20% brown needles, 2 = 20–39% brown needles, 3 = 40–59% brown needles, 4 = 60–79% brown needles and bending of the seedlings terminal shoots, and 5 = 80–100% of brown needles and wilting of the whole seedling [ 22 ]. The seedling assay was conducted twice with 5 replicates for each treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endophytes are plant-associated microorganisms that live in plant tissues without negatively affecting the plant host [9,10]. It has been shown that endophytic microorganisms may control plant pathogens [11][12][13], enhance plant growth [14], and improve phytoremediation. However, previous studies of endophytic bacteria have generally focused on model plants, including Arabidopsis thaliana [15], potatoes [16,17], and soybeans [18], as well as oil-producing trees, including olive trees [19,20], oil palms [21], and Vernicia fordii [22].…”
Section: Introductionmentioning
confidence: 99%